Early recognition of child abuse through screening indicators at the emergency department: experience of a tertiary urban pediatric hospital - Caterina Offidani; Alberto Villani; Antonino Reale; Maria Rosaria Marchili; Lelia Rotondi Aufiero; Patrizio Moras; Maria Lodise; Umberto Raucci; Maria Antonietta Barbieri; Massimiliano Raponi (BMC, 2022)
Abstract Background Emergency Departments play a pivotal role in detecting cases of child abuse. Despite the efforts made in the past decades on the need for a screening method for the early detection of abuse victims, a unique instrument shared by the international scientific community has not been made. These instruments should be able to help recognizing whether it is necessary to further investigate the child's condition. The aim of the study is to illustrate the screening indicators in use since 2010 in the Emergency Department of the Bambino Gesù Children's Hospital to early recognise the victims of abuse and the modifying process of the screening tool undertaken over the years. Methods We retrospectively analyzed the process that led to the editing of the indicators of child abuse in use nowadays at the Bambino Gesù Children's Hospital. We codified three clinical pathways to apply in case of suspected abuse. Furthermore, we investigated the medical records of screening-positive accesses in the Paediatric Emergency Department of the Bambino Gesù Children's Hospital from January 2008 to October 2020. Results An estimation of positive screening, regarding the type of abuse suspected, and the number of accessed in ED was made, resulting in a cohort of 956 patients. In 2010 we created a list of 14 items grouped in three clusters: anamnestic declarations or incongruences, carelessness/neglect and evident lesions at physical examination. Positivity to one of the items allows the actuation of the investigating protocol named as clinical pathway.In 2013, after three years of experience, the criteria were edited to increase specificity. The application of screening led to a median number of 82 suspected cases/year from 2013 to 2020. Conclusion A screening tool is essential and productive for the early recognition of victims of abuse. An in-deep analysis of suspected cases through a standardized method, such as the clinical pathway, allowed reaching the diagnosis in a more accurate and precise manner.